Fuentes Mares y la filosofía de la historia (Sesión inicial del Seminario de Lectura de Textos Filosóficos Mexicanos) - Ordóñez Burgos, Jorge (Chihuahua Hoy, 2019)
Fuentes Mares and the Philosophy of History (Opening session for the Seminar of Mexican Philosophical Texts Reading). Universitary teaching is a scholar activities zone, that recives low care, depreciating its value to contribuite the enrichment of scientific and humanistic investigations. The base of this article is the lectio inauguralis manuscript of Seminar, modificated as philosophcal essay to show reflections on Philosophy of History by Fuentes Mares maked. The text analizes novels, tales, theatrical plays, historical monographies and philosophical books.